Place and Basis for the Formation of Meteorological Vocabulary in the System of French and Uzbek Languages (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Meteonyms are usually widely used in the field of science “meteorology”. Meteorology is the name of the science that studies the atmosphere and climate, and specialists involved in this are called “meteorologists”. Meteorologists are involved in weather forecasting. Explaining the nature of various phenomena occurring in the atmosphere: winds, cyclones, anticyclones and other similar processes is one of the main tasks of meteorologists.